Intermediality in the Metamorphoses. - Dinter, Martin T. (Trends in Classics, 2019)
This article provides an intermedial re-reading of Ovid's Metamorphoses, treating a wide range of passages from Echo and Narcissus in Book 2 to the final sphragis which rounds off Book 15. As its title indicates, the Metamorphoses is at heart a poem about transformations. It is therefore imbued with a sense of dynamism and volatility, which in turn renders it a fertile source of represented intermedial transposition. This chapter explores three processes relating to this wider concept: 'creation', where a medial product is woven, painted, or sculpted, 'human-to-media transformations', which provide a subversive take on intermediality due to their negative connotations, and 'meta-intermediality', through which Ovid comments on media and their narratological potential within the wider poem. By thus problematising medial communication, Ovid identifies and advocates a hierarchy of art forms based on their effectiveness as monumentalising devices: within this system, engravings – owing to their permanence – take precedence over woven or written products. This tendency comes to the fore in the final book of the Metamorphoses, in which Ovid links his poetry to the Fates' records on 'brass and solid iron' (Ov. Met. 15.808–815). In so doing, he does not only assert the authority which his work possesses as a prophecy for Rome's greatness, but also appoints himself as a renowned bard for the ages.